Analysis of The Influence of Personal Factors and The Quality of Health Facilities Services and The Quality of Insurance Services on The Intention to Pay Health Insurance Contributions With Participant Satisfaction as an Intervening Variable - Sasongko Nugroho (International Journal of Social Service and Research, 2023)
Willingness to pay BPJS Health contributions in a timely and continuous manner is very necessary to ensure the sustainability of the JKN program. Personal factors, quality of health facility services, quality of insurance services and customer satisfaction are important factors that influence JKN participants to pay BPJS Health contributions. The aim of this research is to analyze the influence of personal factors and the quality of health facility services as well as the quality of insurance services on the intention to pay health insurance contributions with participant satisfaction as an intervening variable. This research used a purposive sampling method for 286 BPJS Health participants. This research uses an SEM approach using the SmartPLS 3.0 program. The research results show that the quality of insurance services and the quality of health facilities services have a positive and significant effect on participant satisfaction. Apart from that, personal factors also have a positive and significant effect on participant satisfaction. In the context of intention to pay contributions, insurance service quality, service quality and personal factors have a positive and significant influence. The suggestion from this research is to expand the sampling population and types of health facilities to gain broader insight. The managerial implication is that BPJS Health must maintain and improve the quality of services provided to participants, both health facility services and BPJS insurance services themselves. Personal factors of BPJS participants need to be considered, so that they can influence satisfaction and intention to pay contributions consistently